Application of Project-Based Learning Model to Increase Student Activity in Cultural Heritage Materials in Grade V of Elementary School - Indawati, Ninik; Pratiwi, Ameliya Pungki; Mulyanti, Windra Septi (Actual Insight, 2025)
The low activity of students in learning Natural and Social Sciences, particularly in Cultural Heritage materials, remains a common problem in elementary schools. Passive learning has been identified as one of the main factors limiting student engagement. This study aims to improve the activeness of grade V students at an elementary school in Malang City through the application of the Project-Based Learning model in Cultural Heritage materials. The research employed classroom action research using the Kemmis and McTaggart spiral model, conducted in two cycles, each consisting of planning, implementation of actions, observation, and reflection. The study involved 28 students in grade V. Data were collected through observation, interviews, formative tests, and documentation, and were analyzed descriptively, quantitatively, and qualitatively. The results indicated that the application of the Project-Based Learning model increased student activity, with activity percentages rising from 42.8 percent in the pre-cycle stage to 78.5 percent in the first cycle, and reaching 91 percent in the second cycle. These findings demonstrate that the Project-Based Learning model can effectively enhance students’ engagement in science learning, particularly in contextual materials such as Cultural Heritage, while supporting the optimization of project-based learning implementation at the elementary school level.